Molecular mechanisms of radiation resistance in colorectal cancer: in silico identiﬁcation of AURKA, BIRC5 and PLK1 proteins as potential biomarkers - Rodríguez-García, Marta; Burgos-Molina, Antonio Manuel; González Vidal, Alejandro; Sendra-Portero, Francisco; Bernal, Manuel; Ruiz-Gómez, Miguel José (Taylor & Francis, 2025)
Purpose:  The development of radiation resistance by tumor cells severely affects the survival of colorectal cancer patients. The aim of this work is to study the molecular mechanisms involved in the resistance to radiotherapy treatment in colorectal cancer and the identification of key genes as possible biomarkers. Methods:  Data mining was performed in PubMed with the keywords ‘colorectal neoplasms’, ‘radiotherapy’, and ‘resistance’, generating a total of 242 articles in which a series of inclusion and exclusion criteria were applied to select the articles of interest. Then, an in-silico analysis of the selected genes was performed with the bioinformatic tools: GeneCodis, Metascape, KEGG, REACTOME, STRING, STITCH, CHEA3, DGIdb, CTD, and GEPIA. Results:  Different mechanisms and genes involved in radiation resistance were described. These are related to evasion of apoptosis, cell cycle dysregulation, epithelial-mesenchymal transition, and repair of DNA breaks, with the last one being the most relevant and influential. The In-silico study carried out with 21 genes involved in radiation resistance showed the implication of FoxO signaling and EGFR tyrosine kinase inhibitor resistance as the most enriched pathways. In addition, the study identified the key proteins AURKA, BIRC5, and PLK1, showing multiple interacting chemicals and drugs; such as tamoxifen, omacetaxine mepesuccinate, and hydroxyzine pamoate, among others. Conclusion:  The identification of multiple transcription factors that regulate the expression of these key genes as well as the validation in patient samples where higher expression is observed in tumor patients, conserved across tumor stages I-IV, suggests their potential as possible biomarkers.
Keywords: Cáncer colorrectal; Radioterapia; Colorectal cancer; radiotherapy; resistance; ionizing radiation; radiosensitivity; molecular marker